Vernacular Misconceptions in Teaching Science – Types and Causes - CHRZANOWSKI, Marcin M.; GRAJKOWSKI, Wojciech; ŻUCHOWSKI, Szymon; SPALIK, Krzysztof; OSTROWSKA, E. Barbara (Journal of Turkish Science Education, 2018)
The aim of this study was to identify, classify and describe different types of vernacular misconceptions assessed with the items used in a study named Laboratory of Thinking, Diagnosis of Science Education in Poland. We provide an outline of contemporary conceptual change theories and establish a typology of misconceptions where it was distinguished as amphibological, pseudodeictic, hypernimical-hyponimical and contextual ones. The vernacular misconceptions arise when students’ experience problems with the usage of certain scientific language phrases and they may appear in people of all ages, professions and backgrounds. Selected items, together with their detailed description are discussed as well as the possible influence of misconceptions on the students’ learning process.